IMPROVING THE EFFICIENCY OF X-RAY IMAGE ANALYSIS BY CUSTOMS INSTITUTE CADETS USING THE SIMFOX SIMULATOR (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article examines the effectiveness of using the Simfox simulator to improve cadets’ efficiency in analyzing X-ray images at a customs institute. Results show analysis time reduced to 9–13 seconds and detection accuracy increased from 20–30 % to 85–100 %.